Protein Palmitoylation Modification During Viral Infection and Detection Methods of Palmitoylated Proteins - Li, Xiaoling; Shen, Lingyi; Xu, Zhao; Liu, Wei; Li, Aihua; Xu, Jun (Frontiers in Cellular and Infection Microbiology, 2022)
Protein palmitoylation—a lipid modification in which one or more cysteine thiols on a substrate protein are modified to form a thioester with a palmitoyl group—is a significant post-translational biological process. This process regulates the trafficking, subcellular localization, and stability of different proteins in cells. Since palmitoylation participates in various biological processes, it is related to the occurrence and development of multiple diseases. It has been well evidenced that the proteins whose functions are palmitoylation-dependent or directly involved in key proteins’ palmitoylation/depalmitoylation cycle may be a potential source of novel therapeutic drugs for the related diseases. Many researchers have reported palmitoylation of proteins, which are crucial for host-virus interactions during viral infection. Quite a few explorations have focused on figuring out whether targeting the acylation of viral or host proteins might be a strategy to combat viral diseases. All these remarkable achievements in protein palmitoylation have been made to technological advances. This paper gives an overview of protein palmitoylation modification during viral infection and the methods for palmitoylated protein detection. Future challenges and potential developments are proposed.